MEMBANGUN SCIENTIFIC CITIZENSHIP DALAM PENDIDIKAN KEWARGANEGARAAN MELALUI PENDEKATAN CITIZEN SCIENCE DAN EPISTEMIC AGENCY - Heri Ginanjar; Muhamad Akib; Muhamad Ihab Hambali; Grapalda Parasetia Putra; Zulfa Adhiyah N.; Muhammad Gian Pratama (Educatus, 2025)
Civic Education is not only intended to instill national and democratic values but also to prepare citizens who are capable of responding to the challenges of science and technology in the modern era. This study aims to examine the concept of scientific citizenship within the context of Civic Education by integrating the approaches of citizen science and epistemic agency. The research employs a descriptive qualitative method with a literature review as the basis for conceptual analysis. The findings indicate that scientific citizenship encourages students to actively engage in understanding, critically evaluating, and making knowledge-based decisions on public issues such as the environment, health, and digital technology. Through citizen science, students can directly participate in data collection, analysis, and interpretation, thereby fostering critical thinking skills and participatory awareness. Meanwhile, epistemic agency strengthens students’ capacity as active agents in constructing and justifying knowledge. The implications of this study highlight that integrating scientific citizenship into Civic Education broadens the scope of civic competence from normative understanding toward reflective, collaborative, and sustainability-oriented scientific participation. Thus, Civic Education can serve as a strategic platform to develop citizens who are critical, responsible, and scientifically literate in addressing global dynamics within a democratic framework.